2016
DOI: 10.3892/or.2016.5155
|View full text |Cite|
|
Sign up to set email alerts
|

CXCL5 promotes the proliferation and migration of glioma cells in autocrine- and paracrine-dependent manners

Abstract: CXCL5 and its receptor CXCR2 have been found to be involved in tumorigenesis and cancer progression. Recent studies have shown that CXCR2 is upregulated in glioma tissues, and associated with poor prognosis and recurrence. However, the role of CXCL5/CXCR2 signaling in mediating the malignant phenotypes of glioma cells, as well as the underlying mechanism, still remains unclear. In the present study, we found that CXCL5 was upregulated in glioma tissues compared to that noted in normal brain tissues. High CXCL5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
(35 reference statements)
1
34
0
Order By: Relevance
“…The F-box protein FBXL18 promotes glioma progression by promoting K63-linked ubiquitination of Akt [25]. CXCL5 promotes the proliferation and migration of glioma cells [26]. On the other hand, KIAA0247 has been reported to play a tumor suppressing role in proliferation, angiogenesis, and promoting apoptosis of human glioma [27].…”
Section: Discussionmentioning
confidence: 99%
“…The F-box protein FBXL18 promotes glioma progression by promoting K63-linked ubiquitination of Akt [25]. CXCL5 promotes the proliferation and migration of glioma cells [26]. On the other hand, KIAA0247 has been reported to play a tumor suppressing role in proliferation, angiogenesis, and promoting apoptosis of human glioma [27].…”
Section: Discussionmentioning
confidence: 99%
“…C-X-C motif chemokine 5 (CXCL5), is a member of the C-X-C chemokine family, that acts as an important attractant for granulocytic immune cells by binding to its receptor C-X-C Chemokine Receptor Type 2 (CXCR2) [10] . CXCL5 overexpression has been observed in several malignancies, including osteosarcoma, glioma, and lung, bladder, liver, prostate and colorectal cancers [10][11][12][13][14][15][16] , demonstrating its roles in tumor carcinogenesis. Furthermore, CXCL5-CXCR2-dominated cross-talk between cancer cells and macrophages or neutrophils could promote tumor metastases in gastric, hepatocellular and prostate cancers [12,17,18] .…”
Section: Ivyspringmentioning
confidence: 99%
“…According to the previous studies, more than 14 different malignant tumor types, including breast cancer [15], bladder cancer [16], non-small cell lung cancer [17], gastric cancer [18], head and neck squamous cell carcinoma [19], cholangiocarcinoma [20], hepatocellular carcinoma [21], prostate cancer [22], pancreatic cancer [23], colorectal cancer [24], glioma [25], endometrial cancer [26], nasopharyngeal carcinoma [27], and squamous carcinoma of larynx [6], had high expression of CXCL5 when compared to para-carcinoma or normal tissues (Table 1). By identifying and validating the genes regarding the development of gastric cancer, researchers have found that CXCL5, as one of the substances, was associated with early stages of the disease [28].…”
Section: Overexpression Of Cxcl5 In Tumorsmentioning
confidence: 99%